(untitled) (Itinera, 2015)
Why "System and Freedom"? Why "Rationality and Improvisation"? These are the two questions that are at the origin of the conference "System and freedom. Rationality and improvisation between philosophy, art and human practices". The conference, held on 28-31 January 2015 in the premises of the University of Turin and organized by the Center for Philosophical-religious Studies Luigi Pareyson, thanks to funding from the Piedmont Region, and with the sponsorship of the Interuniversity Center of Morphology Francesco Moiso, had a large audience participation. There have been many reasons and reflections reported in this article, on the theme of improvisation and freedom, analyzed from a philosophical point of view. The very high quality of the speeches from the invited speakers (Felix Duque, Universidad Autónoma del Madrid; Luca Illetterati, University of Padua; Davide Sparti, University of Siena; Vincenzo Caporaletti, University of Siena) and of all the speakers, the wide and lively public participation and certainly the intensity of the discussions contributed to the success of this long meeting.